Posted workers on the route to a European labour market: Case study: OSH-related vulnerabilities of posted workers in Spain - Ioana Dodi; Ioana Melenciuc (CES Working Papers, 2019)
The article aims at analyzing the main problems of posted workers in the European Union, especially the elements linked to the relationship between national and European authorities, taking into consideration the European multilevel governance system. The research on which this article is based on is the result of a project that encompasses 9 national study cases, with the aim of understanding how the EU-regulation and national OSH systems affect the health and safety of (posted) workers in a transnational workplace. The data used are gathered through desk-research, as well as fieldwork. The study-case presented within the article is that of Spain. Muddling through the complicated and complex institutional framework, we identified that the main vulnerabilities of the posted workers are related to the a) inequality of payment for the same work; b) poor living conditions; c) cultural and language barriers; d) lack of health insurance and different regulations on work accidents; e) poor representativeness.
Keywords: 330; Posted workers; EU labour market; EU multilevel governance; integration